RESULTS OF CONSERVATIVE TREATMENT OF CONGENITAL HIP DISLOCATION IN INFANTS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
When analyzing the follow-up results of conservative treatment of 84 children with congenital hip dislocation, the highest percentage of satisfactory results (15.4%) and complications (1.2%) was different in patients treated with the Sheptun-Ter-Egnazarov method, taking this into account, the authors have developed an orthopedic abduction splint allowing atraumatic elimination of dislocation of the hip and maintaining movement in the joints during treatment, ensuring movements contributed to the centering of the femoral head in the cavity, which reduced the risk of developing degenerative processes in the joint. When using the proposed orthopedic splint in children from 4 to 12 months in combination with physiotherapy, excellent and good follow-up results were obtained in 7.1 78.6% of cases.